MDA5 Governs the Innate Immune Response to SARS-CoV-2 in Lung Epithelial Cells - Yin, Xin; Riva, Laura; Pu, Yuan; Martin-Sancho, Laura; Kanamune, Jun; Yamamoto, Yuki; Sakai, Kouji; Gotoh, Shimpei; Miorin, Lisa; De Jesus, Paul D.; Yang, Chih-Cheng; Herbert, Kristina M.; et al. (Cell reports (Cambridge), 2021)
Recent studies have profiled the innate immune signatures in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and suggest that cellular responses to viral challenge may affect disease severity. Yet the molecular events that underlie cellular recognition and response to SARS-CoV-2 infection remain to be elucidated. Here, we find that SARS-CoV-2 replication induces a delayed interferon (IFN) response in lung epithelial cells. By screening 16 putative sensors involved in sensing of RNA virus infection, we found that MDA5 and LGP2 primarily regulate IFN induction in response to SARS-CoV-2 infection. Further analyses revealed that viral intermediates specifically activate the IFN response through MDA5-mediated sensing. Additionally, we find that IRF3, IRF5, and NF-κB/p65 are the key transcription factors regulating the IFN response during SARS-CoV-2 infection. In summary, these findings provide critical insights into the molecular basis of the innate immune recognition and signaling response to SARS-CoV-2. [Display omitted] •SARS-CoV-2 replication induces a delayed IFN response in lung epithelial cells•MDA5 and LGP2 are the major sensors recognizing SARS-CoV-2 infection•Viral intermediates activate the IFN response through MDA5-mediated sensing•IRF3, IRF5, and NF-κB/p65 are required for the IFN response induced by SARS-CoV-2 The molecular events that underlie innate immune recognition and response to SARS-CoV-2 infection remain unclear. Yin et al. report that SARS-CoV-2 replication induces a delayed interferon (IFN) response that is triggered by sensing of viral RNA through the MDA5 pattern recognition receptor.